Top ten tips to improve your diet - Clark, Kristine ([Indiana] : Monterey Bay Video Production Co., 2006)
This DVD emphasize the fact that improving the diet is a relatively simple thing to do and that no obsolute rules exist for the perfect diet. Featuring one of the most respected nutritionists in the world and complete in understanding how to eat a more healthy diet and how to be better anle to manage their weight effectively
Title from title screen
Keywords: Health; Nutrition; Diet; Exercise